Mapping self-awareness of cancer-related cognitive impairment: a scoping review of evidence, methods, and neurobiological correlates - Spinetti, Davide; Orzelleca, Mariaines (Frontiers in Neurology, 2025)
BackgroundCancer-related cognitive impairment (CRCI) is a frequent and distressing side effect among cancer survivors. While many patients report persistent cognitive difficulties, a notable discrepancy often exists between subjective complaints and objective performance on neuropsychological testing. This gap raises critical questions about self-awareness and metacognitive insight in the context of CRCI. Despite the clinical relevance of this phenomenon, conceptualized as anosognosia in other neurological conditions, its presence in oncology remains insufficiently explored.ObjectiveThis scoping review aims to map the existing literature on self-awareness of cognitive impairment in cancer survivors, with a focus on studies examining the discrepancy between subjective and objective cognition, the methodologies used to assess awareness, and the clinical and theoretical implications of impaired metacognition in this population.MethodsA systematic search was conducted on PubMed for articles published between 2000 and 2025. Inclusion criteria comprised peer-reviewed studies involving adult cancer survivors that investigated subjective and/or objective cognitive functioning, and addressed aspects of self-awareness, metacognitive monitoring, or anosognosia. Studies were screened, selected, and charted following PRISMA-ScR guidelines.ResultsForty six studies met the inclusion criteria. Most reported a weak or inconsistent correlation between self-reported and objectively measured cognition. A minority employed formal tools to assess metacognitive accuracy or insight. Methodological heterogeneity and a lack of consensus in terminology (e.g., “awareness,” “insight,” “complaints”) limited cross-study comparisons. Only a small number of articles conceptualized this discrepancy in relation to anosognosia or broader models of self-awareness. Factors such as age, mood symptoms, fatigue, and neurobiological correlates (e.g., alterations in the default mode network) were identified as potential moderators of impaired awareness.ConclusionDespite growing evidence of subjective-objective cognitive discrepancies in cancer survivors, the construct of self-awareness remains under-theorized and inconsistently measured in the literature. There is an urgent need for standardization of terms and tools, and for theoretically informed approaches to capture metacognitive impairment in this context. Greater clarity in this domain may inform more tailored interventions, improve survivorship care, and advance the neuropsychological understanding of CRCI.